Annual trends of the Coffee Degree Day and Coffee Borer Degree Day in the equatorial Andean region in Colombia (2015)
It is expected that climate change modifies the current spatial pattern of coffee cultivation in mountainous slopes of Colombia. However, the approaches used to reach these results are based on the use of (global and regional) climate models and species distribution models that largely supported in the niche concept. In order to assess the certainty of the results obtained with these models, a methodology in which data from weather stations and an index of agroclimatic type (thermal time), expressed as degree days are used. The best approximation for thermal time calculation was determined. Then, a multiyear monthly accumulated of coffee degree-days and coffee berry borer degree-days were generated (using the simple triangle method) by using daily data from weather stations with more than 20 years of information. The nonparametric trend analysis (Mann-Kendall) and correlation analysis were used to determine effects of climate variability associated with the occurrence of El Niño and La Niña, on the thermal time of the two mentioned species. Significant,positive trends, in coffee degree-days and coffee berry borer degree-days were found at heights (above sea level) where the optimum coffee growth is reported.